Pengaruh Beberapa Media Tanam Terhadap Pertumbuhan Anakan Kelor (Moringa oleifera L) di Persemaian: The Effect of Several Planting Media on the Growth of Moringa Seedlings (Moringa oleifera L) in Nurseries - Yulianto, Santosa; Sampang; Tanduh, Yusintha; Yulianti, Reri; Rahmawati, Reni (HUTAN TROPIKA, 2025)
Moringa plants (Moringa oleifera L) are multipurpose plants that have many benefits in all parts of the plant, both leaves, stems, seeds, and roots. Apart from being one of the sources of healthy food, beneficial for health, moringa plants can also be used as an alternative energy source for fuel. This study aims to find out the right planting medium for the growth of moringa plant seedlings. This research was carried out in a residential nursery in Bukit Tunggal, Jekan Raya District, Palangka Raya City from January to March 2025. The processing and analysis of data in this study is assisted by MS Excel software and Minitab version 21.1.1. During the research process, observations were made for height increase (cm) and diameter increase (mm), carried out every 2 weeks for 3 months of research. The cumulative number or total samples of this study is 54 Moringa seedlings consisting of 6 planting media treatments, where each of these treatments has 9 Moringa seedling samples. The results showed that the percentage of Moringa seedlings growing during the observation time period and at the end of observation based on the treatment of the planting medium in order, namely PS of 67%, TP 56%, TS and TG equal to 44%, GP 22%, and GB 11%. The response to diameter growth on day 96 (DH-96) was in the interval of 0.15 – 0.3 cm with an average of 0.22 cm. The high growth response on day 96 (TH-96) was in the interval of 13 – 44 cm with an average of 28.88 cm.